PSYCHOLOGICAL AND PSYCHOBIOLOGICAL FACTORS AS A MEASURE OF IRRITABILITY IN THE ATHLETES. - SAHA SOUMENDRA; SAHA, SRILEKHA; AHMED MARUF (International Journal of Pharma and Bio Sciences, 2015)
Present study was undertaken to identify the confounding associations between mood disorders and concomitant psychobiological precursors of inner emotional hindrances observed in high performing athletes of Malaysia. Altogether one-hundred nine male young competitive athletes young competitive athletes volunteered as participants, who were subjected to evaluation of projective analyses of emotionality (in the form of indices of irritability and suspicion); inner psychobiological status (autonomic indices of tonic and phasic skin conductance response habituation paradigm components). Findings of multiple linear regression analyses revealed corroborative relationships between differential psychobiological and inner feelings of suspicion in predicting inner core emotionality. Different Sc indices, such as - tonic and phasic components of skin conductance activity were found to contribute onto the changes observed in the extent of feeling of irritability. Corroborative psychophysiological markers for innate psychological make-up was attempted to be established as differential models in multiple linear regression analyses suggested varied ranges of direct, inverse and supportive relationships between decomposition of autonomic orienting activity components related to affective-motivational aspects of sports behaviour.